POSSIBILITIES FOR THE TRANSFORMATION OF THE SECURITY FORCES IN COLOMBIA FOLLOWING THE POST-CONFLICT PERIOD - Alda Mejias, Sonia (Journal of the Spanish Institute for Strategic Studies, 2018)
This article aims to reflect on how to configure the security forces in Colombia once guerrilla warfare ceases to be the main threat to the country. By analysing the current scenario of insecurity at regional and Colombian level, it intends to demonstrate which forces might be the most suitable for tackling existing threats. Two options were considered: those that cover many different missions, under the heading of multifunction forces and those which, despite their versatility, are specialised forces to address specific threats. Colombia can become a point of reference, gearing the configuration of its forces towards specialisation, as the armed forces model most suitable for addressing the complex insecurity scenario. In order to enable this specialisation, a police force with a military status is proposed, to act alongside the armed forces and the police, as a means to release these forces from missions. This would make it possible to relieve existing forces of the completion of missions for which they are unprepared, while at the same time enabling this third force to specialise, particularly in the prosecution of organised crime.